Implications and Impact of Artificial Intelligence and Sustainable Development in Law & Legal Practice - Arora, Nidhi; Patpatiya, Parth (International Journal of Psychosocial Rehabilitation, 2020)
“Artificial intelligence is changing the manner in which lawyers think, the manner in which they work together and the manner in which they interact with customers. Artificial intelligence is more than legal technology. It is the next incredible concept that will reform the legal profession.”At present, Artificial Intelligence in the legal profession is one of an incredible unfolding opportunity and not a genuine threat, with pioneering adopters providing increasingly proficient and cost-effective legal solutions to an expanding arrangement of existing and potential customers. The utilization of Artificial Intelligence in law is in this manner in the idea of advancement, instead of a transformation. However, beyond a shadow of a doubt – Artificial Intelligence is as of now transforming for all intents and purposes each business and activity that lawyers manage some more rapidly and drastically than others, and the legal profession won’t be saved from this problematic change. The incorporation of Artificial Intelligence into a law company’s systems and operations is a continuous, learning process, so early adopters would have a distinct preferred position over firms that fall behind in adopting the technology.Sustainable development is becoming a necessity for lawyers nowadays. Only a few yet constantly increasing numbers of lawyers are actually doing work related to sustainable development. The present paper discusses the implications and impact of Artificial Intelligence and Sustainable Development in Law & Legal practice.